The Herbal Approachto PCOD: Efficacy, Safety, and Future Directions - Sakshi M. Shetye; Rupali S. Bhoir; Shubham S. Chavan (Asian Journal of Pharmaceutical Research and Development, 2025)
Polycystic ovary syndrome (PCOS/PCOD) is a problem in which a woman’s hormones are out of balance.The pathogenesis is not fully known. Polycystic ovary syndrome is still difficult to diagnose correctly, despite simple diagnostic criteria.The aim of this study is to provide health care as well as substantial evidence that promote the use of herbal remedies to treat Polycystic OvarianSyndrome.A thorough review of the literature was carried out to identify the most relevant information. To ensure the paper's current quality, articles were selected from PubMed, Google Scholar, and other similar databases over eight-year period (2017-2024). This study found that certain plant components contain polyphenolic substances, including isoflavones and flavonoids, that can improve reproductive health in women. Its characteristic featureswhich include irregular menstrual cycles, hirsutism, acne, and chronic anovulationare polycystic ovaries, hyperandrogenism, and infertility. High levels of androgens, or masculine hormones, and insulin resistance are associated with PCOS. Stress, a sedentary lifestyle, inactivity, dietary modifications, and inadequate sleep are additional factors that may contribute. Many plants have shown effectiveness in the treatment of PCOS, including Aloe, Punica granatum, Curcuma longa, Cinnamomum zeylanicum, Tribulus terrestris, Saw palmetto,Berberine. In this review, an attempt has been made to provide a summary of the important medicinal herbs that are used in PCOS treatment or prevention. There is a special emphasis on the role of insulin resistance and the potential benefit of insulin sensitizers in the treatment of PCOS.